Bibliographic Review of Aquatric Systems and their Relevance to the Ivory Coast, a Sub-Saharan African Country - Nobah Céline Sidonie Koco; Koffi Kouakou Barthélemy; Kouakou Affoué Constantine (European Scientific Journal, ESJ, 2024)
Through a review of aquaponic techniques, the present work highlights the interest aroused by this practice in the world as well as different modes of exploitation. Aquaponics is defined as a coupling between a recirculated aquaculture compartment and an aboveground crop compartment. Since two decades, it has been the subject of a significant economic activity in Canada, the USA, Australia and induces numerous research activities. This system is subdivided into three (3) major techniques which are the culture techniques on bed of inert substrates, on nutritive film and that of rafts. Aquaponics is the subject of profitable industrial economic activity on both large and small scale in the USA and Canada. Given the benefits of low water consumption, the non-use of fertilizers and pesticides, aquaponics is unquestionably according to researchers and users, the system capable of revolutionizing livestock farming and agriculture around the world. Côte d'Ivoire is suffering not only from the consequences of climate change but also from rapid urbanization, with the consequent change in water resources. Aquaponics deserves to be mastered then popularized in this country, to help produce fish and plants of better quality while avoiding the waste of water caused by traditional livestock systems.